2004
DOI: 10.1111/j.1462-2920.2004.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecology of soil fungal communities: increased understanding through the application of molecular techniques

Abstract: SummaryFungi fulfil a range of important ecological functions, yet current understanding of fungal biodiversity in soil is limited. Direct DNA extraction from soil, coupled with polymerase chain reaction amplification and community profiling techniques, has proved successful in investigations of bacterial ecology and shows great promise for elucidating the taxonomic and functional characteristics of soil fungal communities. These community profiling techniques include denaturing gradient gel electrophoresis (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
243
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(258 citation statements)
references
References 95 publications
3
243
1
4
Order By: Relevance
“…But the present data along with those of Allen et al (2003), indicate that this is not always true and both have potential bias (Bridge and Spooner 2001; Anderson and Cairney 2004). Hence, a combination of both approaches should probably be adopted in all investigations of this nature so as to ensure the actual endophytic fungi in seagrasses.…”
Section: Discussioncontrasting
confidence: 54%
“…But the present data along with those of Allen et al (2003), indicate that this is not always true and both have potential bias (Bridge and Spooner 2001; Anderson and Cairney 2004). Hence, a combination of both approaches should probably be adopted in all investigations of this nature so as to ensure the actual endophytic fungi in seagrasses.…”
Section: Discussioncontrasting
confidence: 54%
“…They are spread across Ascomycota but were not detected in Saccharomycotina, Taphrinomycotina, the most outlying lineages of Pezizomycotina (Figure 1), or outside of Ascomycota in for example its Dikarya sister group, the Basidiomycota. Some other authors have indicated that, to date, only a small fraction of all endophytes have been detected (Anderson and Cairney 2004; Porras-alfaro and Bayman 2011; Weiss et al 2011). The methods to rapidly detect them have only recently emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular identification through DNA barcoding of fungi has become an integral and essential part of fungal ecology research and has provided new insights into the diversity and ecology of many different groups of fungi (Anderson & Cairney, 2004; Bellemain et al., 2010). Molecular identification has made it possible to study the ecology of fungi in their dominant, but inconspicuous mycelium stage, and not only by observation of fruiting bodies or selective culturing techniques.…”
Section: Discussionmentioning
confidence: 99%